2014
DOI: 10.1007/s11051-014-2472-5
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of aromatic drugs with single-walled carbon nanotubes

Abstract: We report a detailed study of the complexation of aromatic molecules and drugs with the surface of single-walled carbon nanotubes (SWCNTs, the diameter and the length ranges are 0.5-2 nm and 1-5 lm, respectively) in terms of equilibrium binding constants, K. It is found that the binding constants have magnitudes of the order of 10 4 -10 5 M -1 and that there is some ligand specificity to the SWCNT surface depending on the structure of the aromatic molecule. The observed specificity is strongly governed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…The results of the structural analysis performed above, as well as the literature data (e.g. 6,20,21 ), suggest the complex formation of the SWCNT and GO NPs with Dox. We assume that this effect reduces the concentration of free Dox molecules able to induce cell death, thus leading to cell protection from the antibiotic action when Dox is administered together with NPs, as compared with the Dox action as a single agent.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The results of the structural analysis performed above, as well as the literature data (e.g. 6,20,21 ), suggest the complex formation of the SWCNT and GO NPs with Dox. We assume that this effect reduces the concentration of free Dox molecules able to induce cell death, thus leading to cell protection from the antibiotic action when Dox is administered together with NPs, as compared with the Dox action as a single agent.…”
Section: Resultssupporting
confidence: 64%
“…It is known that both, GO and SWCNT, bind small aromatic molecules by formation of π-stacks with them in solution. 6,20,21 The structure of the SWCNT+Dox complex is already known 6 and was not investigated in this work. Hence, further analysis was focused on GO+Dox system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that CNTs are used in biomedicine for cell visualization, drug delivery and bone tissue engineering, there are contradictory views on their toxicity (Kurantowicz et al 2017;Minchenko et al 2018;Prylutska et al 2008;Singla et al 2019). It has been shown that in blood stream, some types of CNTs do not cause negative effects, consequently they are potentially suitable for delivery of drugs or biologically active compounds (Buchelnikov et al 2014;Liu et al 2009;Raphey et al 2019). Low doses of CNTs doped HA nanocrystalline powders do not significantly decrease G-292 cell viability and do not induce oxidative stress after 2 days of exposure (Constanda et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Single‐walled carbon nanotubes are supposed to be the promising pharmacological compounds of a new class with the wide spectrum of therapeutic action . At in vitro studies, it has been shown that single‐walled carbon nanotubes can be adsorbed on the membrane surface, form the transmembrane pores, block the voltage‐gated potassium channels, penetrate into cells, act as neuroprotectors and effective substrates for cultivation of neurons .…”
Section: Introductionmentioning
confidence: 99%